Altered mitochondrial DNA methylation and mitochondrial DNA copy number in an APP/PS1 transgenic mouse model of Alzheimer disease - Xu, YingYing; Xu, LinLin; Han, Min; Liu, XiangTian; Li, Fan; Zhou, XiaoYan; Wang, Yun; Bi, JianZhong (Biochemical and biophysical research communications, 2019)
Alzheimer’s disease (AD) is a chronic neurodegenerative disease and mitochondrial impairment is a key feature of AD. The mitochondrial DNA (mtDNA) epigenetic mechanism is a relatively new field compared to nuclear DNA. The relationship between mtDNA epigenetic mechanism and AD hasn’t been established. So we analyzed the mtDNA methylation in D-loop region and 12 S rRNA gene in the hippocampi in amyloid precursor protein/presenilin 1 (APP/PS1) transgenic mice by bisulfite pyrosequencing. Mitochondrial DNA copy number and gene expression were studied by quantitative real-time PCR (qRT-PCR). We observed a decrease in the displacement loop (D-loop) methylation and an increase in 12 S rRNA gene methylation, while both the mtDNA copy number and the mitochondrial gene expression were reduced in APP/PS1 transgenic mice. In summary, the present finding suggest that mtDNA methylation may play a role in AD pathology, which warrants larger future investigations. •We analyzed the mtDNA methylation in D-loop region and 12 S rRNA gene in the hippocampi in APP/PS1 transgenic mice by bisulfite pyrosequencing.•There were only two studies performed so far to investigate mtDNA D-loop methylation in AD.•And this is the first study to demonstrate a link between the hypermethylation of 12 S rRNA gene and AD.